The Archive for the Psychology of Religion: Editorial principles, practices, and practicalities. (March 2019) - Ladd, Kevin L.
As the Archive for the Psychology of Religion transitions to the SAGE publishing house, this editorial outlines the current vision and principles guiding the way forward. This includes a strong emphasis on publishing work that demonstrates transparency, precision, breadth, and depth in areas of theory, research, and pedagogy. The primary article types are described and the submission practicalities are addressed.